2023
DOI: 10.3390/bs13050413
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated with a Single Joystick-Operated Ride-on-Toy Navigation Training Incorporated into a Constraint-Induced Movement Therapy Program: A Pilot Feasibility Study

Abstract: Our research aims to evaluate the utility of joystick-operated ride-on-toys (ROTs) as therapeutic adjuncts to improve upper extremity (UE) function in children with hemiplegic cerebral palsy (HCP). This study assessed changes in affected UE use and function following a three-week ROT navigation training incorporated into an existing constraint-induced movement therapy (CIMT) camp in 11 children (3–14 years old) with HCP. We report changes in scores on the standardized Shriners Hospital Upper Extremity Evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In the past, we demonstrated the feasibility and positive preliminary effects of singlejoystick-operated ride-on toys (controls provided on the child's affected side) implemented within a modified CIMT camp [27,28]. Given the importance of bimanual skills in daily life, in this study, we incorporated ride-on-toy navigation training using dual joystick controls within a hybrid UE training program to promote bimanual coordination.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the past, we demonstrated the feasibility and positive preliminary effects of singlejoystick-operated ride-on toys (controls provided on the child's affected side) implemented within a modified CIMT camp [27,28]. Given the importance of bimanual skills in daily life, in this study, we incorporated ride-on-toy navigation training using dual joystick controls within a hybrid UE training program to promote bimanual coordination.…”
Section: Discussionmentioning
confidence: 97%
“…We chose ride-on devices because they are popular, intrinsically rewarding, and inclusive toys that promote exploratory play and self-initiated bimanual UE use [47][48][49]. Our training program fostered child autonomy, provided children the "just-right" bimanual motoric challenge and immediate multimodal feedback (visual, auditory, tactile) on their actions, and challenged the children's perceptual, action-related, and motor planning/cognitive skills [27,28,50]. The use of ride-on toys as a therapy adjunct is also aligned with qualitative perspectives shared by children and caregivers that technology and gamification help break the monotony of traditional therapy, fosters greater compliance, promotes sustained engagement during challenging UE activities, and provides a feasible alternative to conventional exercises while fostering repetitive practice [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that a training program using modified, single joystick-operated ride-on toys (with controls provided on the child's affected side) was well-received by children, caregivers, and clinicians. The training was feasible for implementation within an intensive mCIMT program, and in combination with mCIMT, it led to improvements in affected UE use and motor functions assessed using standardized motor tests, arm accelerometry, and video-based measures [36,37]. However, given the importance of bimanual coordination for activities in daily living, the present study will explore the effects of an innovative and playful bimanual ride-on-toy training program among children with CP.…”
Section: Introductionmentioning
confidence: 97%
“…Current evidence on UE rehabilitation approaches in CP suggests that high dose paradigms that foster intensive, task-oriented practice for several hours every day for multiple weeks produce meaningful improvements in function [23,29,30]; however, it is challenging to sustain child engagement and motivation during such intensive paradigms [31][32][33][34]. Over the last several years, our research group has been exploring the use of child-friendly, easy-to-implement, technology-based adjuncts, specifically joystick-operated ride-on toys, to incentivize UE use, boost treatment dosing, and promote task-oriented UE practice through incrementally challenging navigational games [35][36][37]. Previously, we reported that a training program using modified, single joystick-operated ride-on toys (with controls provided on the child's affected side) was well-received by children, caregivers, and clinicians.…”
Section: Introductionmentioning
confidence: 99%